2015
DOI: 10.7762/cnr.2015.4.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake Assessment and Biochemical Characteristics of Blood and Urine in Patients with Chronic Gastritis

Abstract: Chronic gastritis is a prevalent gastroentestinal disease in Korea. The purpose of this study was to investigate status of foods and nutrients intake and health related biochemical indicators in the patients with chronic gastritis. Daily food and nutrient intake, blood lipids, and antioxidant indicators in the urine, were compared between a group of 19 patients diagnosed with chronic gastritis and a control group of 27 subjects having normal gastroscopy. No significant differences were found in age, height, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Foods with high-fat act on retardation of gastric emptying and the broths with large quantities of purine raise the acid secretion. Therefore, spicy foods and high-fat foods are not recommended (Ddine et al, 2012;Choi et al, 2015). Spicy food increases gastric secretion and causes constant irritations in the mucosa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foods with high-fat act on retardation of gastric emptying and the broths with large quantities of purine raise the acid secretion. Therefore, spicy foods and high-fat foods are not recommended (Ddine et al, 2012;Choi et al, 2015). Spicy food increases gastric secretion and causes constant irritations in the mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…Information regarding the use of tea, spicy and oily foods, and soda bottles. 4. Contributing symptoms like bad taste, heartburn, vomiting, abdominal bloating and stomach ache, indigestion, constipation, loss of weight, feel swelling in the stomach.…”
Section: Methodsmentioning
confidence: 99%
“…The mean dietary spice intake was 34.19±22.18 g/day using 24-hour dietary recall. In 2018, a study from China among people more than 65 years of age reported the IQR for spice intake was 0-16.7 [ 3 ]. This discrepancy reflects the demographic and geographic distribution of study participants and preferences for spicy food In India, Guntur, Andhra Pradesh is known as the “Chilli city” and is known across the world for its chili growers.…”
Section: Discussionmentioning
confidence: 99%
“…But the main cause of this CG is an infection due to the Helicobacter pylori bacterium [ 3 ]. Dietary factors such as the intake of spicy food that is food in spices/condiments which irritate the mucosal lining of the stomach could lead to such conditions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that diet plays an important role in the etiology of chronic inflammation of the gastric mucosa [22][23][24][25][26][27][28][29][30][31]. A high-fat diet impairs the gastrointestinal tract by producing bile acids, resulting in the expression of pro-inflammatory enzymes and cytokines that contribute to the development of insulin resistance [22].…”
Section: Introductionmentioning
confidence: 99%